Meningkatkan Kepuasan Pengguna Layanan Publik melalui Fasilitas dengan Kualitas Layanan sebagai Variabel Interverning di Kantor Kecamatan Bandung - Ardiasih, Avita Putri; Cahyoadi, Bayu (Universitas Negeri Surabaya, 2024)
Public service user satisfaction is a benchmark for the success of services in a public agency. The purpose of this study was to determine the effect of facilities on public service user satisfaction at the Bandung District Office; to determine the effect of facilities on public service quality at the Bandung District Office; to determine the effect of service quality on public service user satisfaction at the Bandung District Office. Data collection using a questionnaire of 200 respondents. This research uses Structural Equation Modeling (SEM) with AMOS 26.0 software. The results of data processing concluded that there is an influence between facility variables on public service user satisfaction at the Bandung District Office; there is an influence between facility variables on service quality at the Bandung District Office; there is an influence between service quality variables on public service user satisfaction at the Bandung District Office.